2020
DOI: 10.1093/pm/pnaa089
|View full text |Cite
|
Sign up to set email alerts
|

Is Buprenorphine Effective for Chronic Pain? A Systematic Review and Meta-analysis

Abstract: Objective The objective was to perform a systematic review and meta-analysis of the literature on the effects of buprenorphine on chronic pain outcomes (i.e., patient-reported pain intensity) in patients with and without opioid use disorder (OUD). Design Ovid/Medline, PubMed, Embase, and the Cochrane Library were searched for studies that explored the effectiveness (in reducing pain) of buprenorphine treatment for chronic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…However, it should be noted that there is evidence to suggest that buprenorphine is relatively ineffective at reducing pain intensity in patients with comorbid opioid use disorder. 36 Given that pain appears to be the driver for aberrant behaviours in this group, these patients may find non-pharmacological interventions – such as physical therapy and training in self-management strategies – to be more effective in managing their pain while reducing the risk of exacerbating their OD. It is difficult to comment in detail on the appropriateness of methadone treatment for the ODD→CP group, and future studies should consider comparing functional outcomes in this group with those of ODD patients with no pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that there is evidence to suggest that buprenorphine is relatively ineffective at reducing pain intensity in patients with comorbid opioid use disorder. 36 Given that pain appears to be the driver for aberrant behaviours in this group, these patients may find non-pharmacological interventions – such as physical therapy and training in self-management strategies – to be more effective in managing their pain while reducing the risk of exacerbating their OD. It is difficult to comment in detail on the appropriateness of methadone treatment for the ODD→CP group, and future studies should consider comparing functional outcomes in this group with those of ODD patients with no pain.…”
Section: Discussionmentioning
confidence: 99%
“…49,51,[59][60][61] In a meta-analysis examining the effects of buprenorphine (SL, transdermal, and buccal) on chronic pain outcomes in patients with or without opioid use disorder (OUD), the authors found that efficacy was more pronounced in patients without OUD, and high doses may be needed for patients with OUD. 62 Overall, the data from these studies suggest that buprenorphine has equivalent or greater clinical analgesic efficacy than conventional opioids.…”
Section: Benefit-risk Assessment Of Buprenorphine Vs Conventional Opioids Efficacymentioning
confidence: 93%
“…Those with chronic pain also benefit less from MOUD in comparison to those without chronic pain, suggesting there may be additional treatment needs (Ilgen et al, 2006). Finally, MOUD appears to have limited analgesic effects in those with OUD and chronic pain (Lazaridou et al, 2020). Therefore, MOUD alone may be insufficient for the management of co-occurring OUD and chronic pain.…”
mentioning
confidence: 99%
“…It was also hypothesized that a majority of the sample would transition between the high and low pain interference profiles over the course of treatment, given that BUP/NX and the study treatment have been shown to promote opioid abstinence and lifestyle changes leading to improved quality of life (Volkow et al, 2019; Weiss et al, 2011). Further, the pain intensity profiles would remain stable over the course of treatment, given that BUP/NX has a limited effect on pain intensity (Lazaridou et al, 2020) and the study treatment involved only one session of pain coping skills.…”
mentioning
confidence: 99%